2005
DOI: 10.1128/mcb.25.10.4034-4045.2005
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Functional Gap Junctions through Internal Ribosome Entry Site-Dependent Synthesis of Endogenous Connexins in Density-Inhibited Cancer Cells

Abstract: Gap junctions are composed of connexins and are critical for the maintenance of the differentiated state. Consistently, connexin expression is impaired in most cancer cells, and forced expression of connexins following cDNA transfection reverses the tumor phenotype. We have found that the restoration of density inhibition of human pancreatic cancer cells by the antiproliferative somatostatin receptor 2 (sst2) is due to overexpression of endogenous connexins Cx26 and Cx43 and consequent formation of functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 58 publications
1
36
0
1
Order By: Relevance
“…As sst2 normally triggers antiproliferative signals (17), its absence leads to uncontrolled cell proliferation. We have however shown that sst2 reexpression conversely limits the proliferation of pancreatic cancer cells, likely via the induction of 4E-BP1 protein and the restoration of contact inhibition (18). Here, we first wish to confirm that sst2-triggered contact inhibition is dependent on 4E-BP1 protein accumulation.…”
Section: Characterization Of the Model Of Cell Density-dependent Accumentioning
confidence: 62%
“…As sst2 normally triggers antiproliferative signals (17), its absence leads to uncontrolled cell proliferation. We have however shown that sst2 reexpression conversely limits the proliferation of pancreatic cancer cells, likely via the induction of 4E-BP1 protein and the restoration of contact inhibition (18). Here, we first wish to confirm that sst2-triggered contact inhibition is dependent on 4E-BP1 protein accumulation.…”
Section: Characterization Of the Model Of Cell Density-dependent Accumentioning
confidence: 62%
“…S3) (46,47). Coculture and flow cytometric analysis of Cy3-siRNA transfer was repeated following pretreatment with AGA prior to a 90-min coculture at 37°C, as described above.…”
Section: Analysis Of Stable Hek293-derived Transfectant Cellmentioning
confidence: 99%
“…1 A and B). We have previously demonstrated that the inhibitor of cap-dependent translation 4E-BP1 is activated in BxPC-3/sst2 cells, sst2 increasing both its transcriptional expression, and its activity by repressing PI3K activity (17,18). Furthermore, treatment of BxPC-3 cells with the mTOR inhibitor, rapamycin, which inhibits 4E-BP1 activity, does not affect TSP-1 expression, suggesting a cap-independent process in the control of TSP-1 mRNA translation.…”
Section: Molecular Mechanisms For Sst2-dependent Upregulation Of Tsp-1mentioning
confidence: 98%